Правові засади формування парламентських комітетів (комісій) у різних країнах - Зозуля, О. І.; Zozulia, O. I.; ORCID: http://orcid.org/0000-0002-5428-4622 (Visegrad journal on human rights. – 2019. - № 1 (Vol. 1). - P. 42-47, 2019)
У статті виконано порівняльно-правовий аналіз конституційно-правових засад формування парламентських комітетів (комісій) у різних країнах, визначено їх основні спільні та відмінні риси, встановлено особливості організації та складу, а також обґрунтовано пріоритетні напрями удосконалення інституту парламентських комітетів, зокрема, й конституційно-правового статусу комітетів Верховної Ради України.

The comparative-legal analysis of the constitutional-legal basis of the formation of parliamentary committees (commissions) in different countries is made, also it was defined its main general and distinctive features, the peculiarities of organization and composition are determined, as well as substantiated priority directions of improvement the institution of parliamentary committees, including the constitutional-legal status of committees of the Verkhovna Rada of Ukraine.

В статье выполнен сравнительно-правовой анализ конституционно-правовых основ формирования парламентских комитетов (комиссий) в разных странах, определены их основные общие и отличительные черты, установлены особенности организации и состава, а также обоснованы приоритетные направления совершенствования института парламентских комитетов, в частности, и конституционно-правового статуса комитетов Верховной Рады Украины.
Legal basis forming parliamentary committees (commissions) in different countries
Zozulia, O. Правові засади формування парламентських комітетів (комісій) у різних країнах = Legal basis forming parliamentary committees (commissions) in different countries / Oleksandr Zozulia // Visegrad journal on human rights. – 2019. - № 1 (Vol. 1). - P. 42-47
Keywords: Конституційне право. Constitutional Law. Конституционное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; зарубіжний досвід; зарубежный опыт; foreign experience; парламент; parliament; тимчасові комісії; Верховна Рада України; committees; temporary committees; Verkhovna Rada of Ukraine; временные комиссии